Exploring Students' Perceptions and Interest in the Merdeka Belajar Kampus Merdeka (MBKM) Program: A Case Study at Universitas Islam Nusantara - Agus Ruswandi; Hendi Suhendraya Muchtar; Agus Mulyanto; Riki Ruswandi (AL-ISHLAH: Jurnal Pendidikan, 2025)
The Merdeka Belajar Kampus Merdeka (MBKM) program is a national initiative aimed at aligning higher education outcomes with workforce demands. However, at Universitas Islam Nusantara, student participation in MBKM remains low. This study investigates the perceptions, interest, and readiness of students—factors that may influence their engagement in the program. This study employed a quantitative survey design using a cross-sectional approach. Data were collected through an online questionnaire distributed to 207 students from three study programs within the Faculty of Teacher Training and Education. The sample was determined using the Isaac and Michael formula with a 1% error margin. Data were analyzed descriptively. Findings indicate that students’ perceptions of the MBKM program are varied and lack a dominant consensus. While 54.11% of respondents viewed the program as "very useful," only 21.26% considered it "very important" for future employment. Additionally, student knowledge about MBKM is limited, with only 0.97% claiming full awareness of the program. Interest was highest in internship (44.93%), student exchange (41.06%), and teaching assistantship (40.10%) activities. Overall, 63.77% of students expressed a strong interest in MBKM, yet only 31.40% felt ready to participate. The study highlights a gap between student interest and readiness, potentially due to limited socialization and understanding of the program. Enhanced communication strategies and institutional support are recommended to increase student engagement in MBKM.